Simultaneous removal of copper and lead from an aqueous solution using low-cost adsorbents - Mohd Amin, Adrah (2010)
The presence of heavy metals in waste water is known to cause severe damage to aquatic life, beside the fact that these metals kill microorganism during biological treatment of waste water with a consequent time delay of the treatment process. Hence this paper aims to ascertain the feasibility of using low-cost adsorbents for simultaneous removal of copper and lead from an aqueous solution. In this work, sawdust and peanut shells were used as low-cost adsorbents, which are abundant in nature, or are a byproduct or waste material from another industry. The experiments were conducted using batch adsorption method. The effect of contact time, agitation rate and pH on the simultaneous removal of copper and lead were studied. The experimental results concluded that the better adsorption efficiency was obtained only after 60 minutes of contact time for both the adsorbents. Furthermore, the adsorption of copper and lead increased with increase in agitation rate for sawdust, but for peanut shells the effect of agitation rate was negligible. The maximum removal of copper and lead on sawdust was achieved when pH is 6, whereas for peanut shells when pH is 3.